Percepção sensorial de cafés especiais utilizando avaliadores treinados e não treinados - Monferdini, Luiz Henrique Nicolella (Universidade Federal de São Carlos, 2025)
The study aimed to compare analysis notes from trained and untrained evaluators, using the Specialty Coffee Association – SCA sensory evaluation form on 5 specialty coffees obtained by drying peeled cherries. 30 mL of each coffee drink (filtered) were served to 10 trained evaluators and 10 untrained evaluators. The trained evaluators identified more complex attributes, such as chocolate, caramel, vanilla and fruity and the untrained evaluators mainly pointed out characteristics such as sweetness. The overall score from the evaluators of the 5 coffees, regardless of the group, was above 80 points. The peeled cherry processing method influences the sensory characteristics, highlighting the importance of the diversity of sensory perception and that processing is directly linked to the quality of the coffee. The results of this study showed the importance of considering the diversity of preferences and the impact of processing on the final quality of specialty coffee, showing that both professionals and untrained evaluators can differentiate different aspects of the same product. It is concluded that, despite differences in perception, both groups recognized the sensorial quality of the coffees.
Sensory perception of specialty coffee using trained and untrained evaluators
Keywords: Análise sensorial; Secagem; Coffea arabica L.; Sensory analysis; Drying; Cherry-peeled; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::AVALIACAO E CONTROLE DE QUALIDADE DE ALIMENTOS